Kajian Pemberian Stretomyces Spp Terhadap Perkembangan Gejala Penyakit Layu Fusarium Pada Tanaman Melon (Cucumis Melo L.) - Penta SURYAMINARSIH; Tri MUJOKO; Dewi ANGGRAENI (Jurnal Pengendalian Hayati, 2008)
In the century, chemistry method often was done to control fusarium wilt deseases inMelo (Rukmana dan Saputra 1997). It has negative effect to the environment (Novizar, 2002). Once ofthe control method that is often been researche is antagonis microorganism using and streeptomyces isbiological agens which is in actinomycetes group. Fusarium fungi can survive many years asClamidospora in the soil (Semangun 1994 and Kranz 1977). Appearing wilt symptom caused byFusarium infection in parenchym of the bottom stemp. Using of Streeptomyces as biological agenscan control spreading of Fusarium wilt symptom.The aim of the research was to know optimum dosage of streeptomyces givedto fusarium wiltsymptom in melo plant (Cucumis melo L.). The research had been done for six months, December2006 until May 2007 at experimental land of UPN “Veteran” East Java. Completely Randomizedesign was used. The Treatment was streeptomyces dosage consist of 2 gr/3 Kg soil. 4 gr/3 Kg, 6gr/3kg, 8 gr/3kg, 10 gr/3 Kg, and every treatment was done five times. Streptomyces isolation wastaken from 5 – 15 Cm deep soil of Wajak – Tulungagung.Observation was done once time a week toWilt leaf Symtom and discoloration length of steem.Based of the observation, The Conclution is 6 grStreeptomyces/3 Kg soil more effective than the other dosage of streeptomyces gived.